Heterogeneous C-H functionalization in water via porous covalent organic framework nanofilms: a case of catalytic sphere transmutation - Sasmal, Himadri Sekhar; Bag, Saikat; Chandra, Bittu; Majumder, Poulami; Kuiry, Himangshu; Karak, Suvendu; Sen Gupta, Sayam; Banerjee, Rahul (Journal of the American Chemical Society, 2021)
Heterogeneous catalysis in water has not been explored beyond certain advantages such as recyclability and recovery of the catalysts from the reaction medium. Moreover, poor yield, extremely low selectivity, and active catalytic site deactivation further underrate the heterogeneous catalysis in water. Considering these facts, we have designed and synthesized solution-dispersible porous covalent organic framework (COF) nanospheres. We have used their distinctive morphology and dispersibility to functionalize unactivated C-H bonds of alkanes heterogeneously with high catalytic yield (42-99%) and enhanced regioand stereoselectivity (3 degrees:2 degrees = 105:1 for adamantane). Further, the fabrication of catalyst-immobilized COF nanofilms via covalent self-assembly of catalytic COF nanospheres for the first time has become the key toward converting the catalytically inactive homogeneous catalysts into active and effective heterogeneous catalysts operating in water. This unique covalent self-assembly occurs through the protrusion of the fibers at the interface of two nanospheres, transmuting the catalytic spheres into films without any leaching of catalyst molecules. The catalyst-immobilized porous COF nanofilms' chemical functionality and hydrophobic environment stabilize the high-valent transient active oxoiron(V) intermediate in water and restricts the active catalytic site's deactivation. These COF nanofilms functionalize the unactivated C-H bonds in water with a high catalytic yield (45-99%) and with a high degree of selectivity (cis:trans = 155:1; 3 degrees:2 degrees = 257:1, for cis-1,2-dimethylcyclohexane). To establish this approach's ``practical implementation'', we conducted the catalysis inflow (TON = 424 +/- 5) using catalyst-immobilized COF nanofilms fabricated on a macroporous polymeric support.

Electrocatalytic alcohol oxidation by a molecular iron complex - Kuiry, Himangshu; Das, Debasree; Das, Soumadip; Chakraborty, Soham; Chandra, Bittu; Sen Gupta, Sayam (Faraday Discussions, 2022)
An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe-III-OH2](-), as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. The substrate scope also includes alcohols that contain O and N heteroatoms in the scaffold, which are well tolerated under these reaction conditions. Mechanistic studies show the involvement of a high-valent Fe-V(O) species, [(bTAML)Fe-V(O)](-), formed via PCET (overall 2H(+)/2e(-)) from [(bTAML)Fe-III-OH2](-) at 0.77 V (vs. Fc(+)/Fc). Moreover, electrokinetic studies of the oxidation of C-H bonds indicate a second-order reaction, with the C-H abstraction by Fe-V(O) being the rate-determining step. The overall mechanism, studied using linear free energy relationships and radical clocks, indicates a ``net hydride'' transfer, leading to the oxidation of the alcohol to the corresponding aldehyde or ketone. When the reaction was carried out at pH > 11, the reaction could be carried out at a similar to 500 mV lower potential than that at pH 8, albeit with reduced reaction rates. The reactive intermediate involved at pH > 11 is the corresponding one-electron oxidized [(bTAML)Fe-IV(O)](2-) species.